Evaluation of Triggering Associates of Dental Anxiety and Fear (Journal of Pharmaceutical Negative Results, 2023)
Background Dental anxiety and fear complement each other in the literature. Children often associate dentistry with pain. The position of the dental chair makes them feel nervous and claustrophobic. They feel anxious due to lack of control of the situation. Materials and Methods Study design was cross-sectional in nature. A reliable and valid self administered questionnaire was used.It was conducted on 120 children, in Chennai city. A set of five close-ended questions pertaining to dental anxiety and fear was designed in a sequential and logical order. The responses were recorded as Likert based responses. Results Data were analyzed using SPSS version 20. (IBM, India). Chi-square test was used to compare the qualitative data, to find out the statistical significance. Strength of association was also computed. The level of significance was set at P < 0.05.For independent association with outcome multivariate logistic regression was used. The prevalence in boys was 50.4 % and in girls it was 71.2 %. The triggering factors contributed largely to dental anxiety and fear. Conclusion The present study concludes that identifying the barriers of dental anxiety will help in reducing dental anxiety in children.